Motorcycle Sales Accounting Information System Design at CV. Mother of Medan - Sabaruddin Ahmad Dolok Saribu (Trigin Publisher, 2023)
The development of sophisticated science and technology is now felt by users of a computer-based information technology. With today's technological sophistication, every company and public service agency is required so that all work can be completed in a computerized system. CV. Bunda Medan is a company engaged in the sale of motorcycles. Problem formulation in CV. Mother of Medan is that a computerized system has not been created in conducting sales transactions so that work is still not effective and efficient. To overcome the problems that exist in the CV. Mother Medan the author wishes to create a new information system. To create an information system the author uses the VB programming language. 2008 with MySQL Database. The purpose of making this system is to facilitate the transaction and sales data processing. The reports generated are also more accurate.